A frog in hot water: the effect of temperature elevation on the adrenal stress response of an African amphibian - Scheun, Juan; Venter, Leanne; Ganswindt, Andre (PeerJ, 2024)
Amphibians, with their unique physiology and habitat requirements, are especially vulnerable to changes in environmental temperatures. While the activation of the physiological stress response can help to mitigate the impact of such habitat alteration, chronic production of elevated glucocorticoid levels can be deleterious in nature. There is no empirical evidence indicating the physiological response of African amphibians to temperature changes, where individuals are unable to emigrate away from potential stressors. To rectify this, we used the edible bullfrog (Pyxicephalus edulis) as a model species to determine the effect of elevated temperature on the adrenocortical response of the species using a recently established matrix. While a control group was kept at a constant temperature (25 °C) throughout the study period, an experimental group was exposed to control (25 °C) and elevated temperatures (30 °C). Mucous swabs were collected throughout the study period to determine dermal glucocorticoid (dGC) concentrations, as a proxy for physiological stress. In addition to this, individual body mass measurements were collected. The results showed that individuals within the experimental group who experienced increased temperatures had significantly elevated dGC levels compared to the control animals. Furthermore, there was a significant difference in the percentage mass change between experimental and control animals . These findings indicate the physiological sensitivity of the edible bullfrog to a thermal stressor in captivity. While this study shows the importance of proper amphibian management within the captive environment, it also highlights the coming danger of global climate change to this and similar amphibian species.
Keywords: Non-invasive; Mucous; Thermal stressor; Bullfrog; Stress response; Weight loss